How do the industrial land use intensity and dominant industries guide the urban land use? Evidences from 19 industrial land categories in ten cities of China. (February 2020) - Yin, Guanyi; Lin, Zhulu; Jiang, Xilong; Qiu, Menglong; Sun, Jin
Highlights: The industrial land categories were classified based on industrial activities. A framework for evaluating the industrial land use intensity was established. The Location Quotient method was applied to identify the dominant industries in cities. Abstract: Facing with scarce urban land resources, quantitative evaluating the industrial land use intensity is crucial to sustainable urban land use. In this study, ten cities with different development levels in China, Zhenjiang, Weinan, Guangzhou, Tonghua, Tongliao, Liaocheng, Taiyuan, Puyang, Zhuzhou, were chosen as the study cases. The industrial land use intensity (ILUI) of these cities were assessed by a comprehensive evaluation framework, and dominant industries were recognized by the method of Location Quotient. The results showed that a conspicuous unbalanced ILUI index was observed in these cities, with the highest index in Guangzhou and the lowest in Liaocheng. Moreover, the total scale, internal structure, layout and economic intensity of industrial land did not coordinate with each other, which indicated that inner-city land use feature varies. In addition, the Water conservancy, environment and public facilities management industry, the Information transmission, software and information technology services industry and the Renting and Commercial Services industry were recognized as the common dominant industries among these cities. This study could provide an insight of the gap between current industrial land use pattern and balanced intensive industrial land use pattern, to use the urban land more sustainable in the future.